IL-15 in alopecia areata: the immune tolerance mechanistic insights and translational perspectives - Jiahua Fan; Yang Luo; Chong Gao; Yanqing Wang (Frontiers in Medicine, 2026)
Alopecia areata (AA) is a highly prevalent human autoimmune disease. It is now regarded by most scientists as a defect of immune privilege (IP). The impaired IP in the hair follicles is an essential driver of AA, which is developed by the imbalanced local CD8 + T cell, NK cell, tissue-resident Treg cells and infiltration of many factors such as IFN- γ and TGF- β . In the past, IL-2 and IL-15 are generally recognized for their roles in promoting pro-inflammatory immune responses. Moreover, cytokine-based therapeutic strategies utilizing IL-2 or IL-15 have the capacity to expand effector T cell and NK cells, thereby offering a viable alternative immunotherapeutic approach for cancer treatment. In contemporary century, there has been a gradually growing recognition of their critical role in modulating immune tolerance (via Treg cell). Low-dose IL-2 preferentially induces Treg cell, recovering the balance status between Treg cell and effector T cell and representing an original strategy for autoimmune systematic diseases. Recent study found IL-15 was the guardian of IP in hair follicles arousing the attention of IL-15 in maintain immune tolerance. IL-15, as a pleiotropic cytokine, shares many overlapping biological functions with IL-2. Notably, IL-15 will replace IL-2 to play a certain role while the level and function of IL-2 has decreased. Low-dose IL-2 and certain concentration of IL-15 complement each other, maintaining the function of Treg cell, and induce reconstruction in immune tolerance, which may be a new strategy for treating alopecia areata. Therefore, refocusing on the function of IL-15 and its role in AA might provide new insights into the pathogenesis and therapy of AA.